2020
DOI: 10.1108/ijchm-02-2020-0142
|View full text |Cite
|
Sign up to set email alerts
|

The motives behind consumers’ intention to use peer-to-peer accommodation: an fsQCA application

Abstract: Purpose Literature on the motives influencing consumers’ intention to use peer-to-peer (P2P) platforms has become vast and fragmented. The purpose of this paper is to shed light on this research stream by applying a novel methodological approach that reveals the existence of alternative combinations of motives that equally boost consumers’ intention to use P2P accommodation. Design/methodology/approach The methodological approach builds on the complexity theory and includes both linear and nonlinear techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 75 publications
1
41
1
Order By: Relevance
“…In this way, our research outcome is not only more consistent with what logic might imply,but also more instructive for improving the China's software industry [15]. Thirdly, fsQCA focuses on the asymmetric causal relationship between causes and effects, which breaks through the limitations of the symmetric thinking based on correlation coefficient in traditional quantitative research [16]- [17].…”
Section: Introductionsupporting
confidence: 59%
“…In this way, our research outcome is not only more consistent with what logic might imply,but also more instructive for improving the China's software industry [15]. Thirdly, fsQCA focuses on the asymmetric causal relationship between causes and effects, which breaks through the limitations of the symmetric thinking based on correlation coefficient in traditional quantitative research [16]- [17].…”
Section: Introductionsupporting
confidence: 59%
“…Recent years have seen a significant increase in fsQCA applications in various social science disciplines (Farmaki et al, 2021;Kadile and Biraglia, 2020;Mikalef and Pateli, 2017;Pappas et al, 2019;Phung et al, 2020;Xie and Wang, 2020), especially in the field of hospitality and tourism (Olya, 2020;Rasoolimanesh et al, 2020). In this field, researchers have applied fsQCA in different contexts, such as evaluating travelers' willingness to pay (Agag et al, 2020), tourism accommodation services (Pappas and Papatheodorou, 2017), festival management (Gannon et al, 2019;, tourist behavior in green hotels (Olya et al, 2019a), peer-to-peer accommodation (De Canio et al, 2020;Pappas, 2017), medical tourism (Olya and Nia, 2020) and tourist engagement (Rasoolimanesh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Another stream of research has focused on user behaviors and decisions in peer-to-peer rental platforms. Some studies have examined the motivation for users to use or to discontinue using peer-to-peer rental platforms and have summarized the characteristics of users of such platforms (Boateng et al , 2019; De Canio et al , 2020; Huang et al , 2020; So et al , 2019). From the perspective of properties and hosts, many studies have observed how host and property characteristics such as price and service quality influence a property’s reputation and performance (Liang et al , 2017, 2020b; Ranjbari et al , 2020; Xie and Mao, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%